PEMANFAATAN PETA BALI SEBAGAI MEDIA PEMBELAJARAN IPS: STUDI OBSERVASI DI MI AL HIDAYAH CIPACUNG - Khalidah Safa Ramadani; Fitri Nopianti; Ajeng Tri Septiani; Wina Nurkholifah; Najwa Azkiatul Fadilah; Vina Berliviana; Sun’Ah; Ratna Dewi (Jurnal Padamu Negeri, 2025)
This study aims to describe the use of the Bali map as a learning medium in Social Science (IPS) subjects at MI Al Hidayah Cipacung. The research employed a qualitative approach through participatory observation, documentation, and informal interviews. The results show that using the Bali map improves students’ understanding of geographical positions, temples, districts, and Bali’s socio-cultural elements. The map also stimulates active interaction, group discussions, and increases students’ curiosity. The teacher’s strategy of integrating maps into small project-based learning helped build students’ analytical and collaborative skills. Challenges found include limited map availability and the absence of interactive digital maps. The study recommends developing varied and contextual map media to support effective IPS learning.